The effects of substituting spray-dried whole egg from egg grading plants for spray-dried plasma protein in phase I diets - W B Nessmith Jr; J R Bergstrom; K Q Owen; B T Richert; J W Smith II; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1995)
A study was conducted to evaluate the effects of replacing spray-dried plasma protein with spray-dried whole egg from egg grading plants on starter pig performance. Up to 50% (3.5% of the diet) of spray-dried plasma protein can be replaced with spraydried whole egg (6% of the diet) without influencing performance of starter pigs.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Starter; Plasma protein; Egg protein